Design of the metro tunnel project tunnel linings for fire testing. (14th August 2020) - Guerrieri, Maurice; Sanabria, Carlos; Lee, Wei Ming; Pazmino, Esteban; Patel, Rahul
Abstract: With a growing pipeline of major transport infrastructure projects transforming Victoria's road and rail networks, there is an increase in demand for the construction of underground tunnels using the shield tunneling method. Such tunnels need to be designed for fire resistance in order to preserve both structural integrity and serviceability in the event of a fire event. This paper describes the approach taken to design the concrete tunnel lining segments for Melbourne's Metro Tunnel Project for structural stability during a severe fire incident. Two types of fire testing programs were implemented, both of which used the RABT ZTV (rail) fire curve. The first involved the fire testing of 12 unloaded flat panels in order to determine whether a particular concrete mix design would be susceptible to spalling. Second, six prototype full scale tunnel lining segments were subjected to full scale structural fire testing, for the first time in Australia. The results indicated that full scale structurally loaded fire tests are essential as unloaded flat panels underestimate the degree of spalling. Addition of PP fibers are successful in mitigating spalling in addition to using pozzolans cements such as flyash and slag.